Inclusão da educação especial em projetos pedagógicos dos cursos de pedagogia da Ufopa - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
This research focuses on the study of inclusive Special Education processes included in the Pedagogical Course Projects (PPCs) of the Pedagogy Degree Programs at the Federal University of Western Pará (UFOPA), Santarém and Óbidos campuses. It raises the following research problem: how is the teacher training process for the inclusion of Human Groups in Special Education (GHEE) reflected in the Pedagogical Course Projects (PPCs) of the Pedagogy programs at UFOPA, Santarém and Óbidos campuses? The aim is to investigate how the teacher training process for the inclusion of Human Groups in Special Education (GHEE) is reflected in the Pedagogical Course Projects (PPCs) of the Pedagogy programs at UFOPA, Santarém and Óbidos campuses. Specifically, it seeks to verify the presence of Special Education elements from the perspective of Inclusive Education in these PPCs; To identify, in the PPCs, the principles that comprise the training of educators for the inclusion of GHEE; and to verify what Brazilian legislation provides for the training process of educators in inclusive contexts of Special Education. This is a qualitative, bibliographic study (Rodrigues, França 2010). Among the results, it was found that PPCs 1 and 2 provide guiding elements for the inclusion of GHEE, as well as inclusion, adding markers of ethnic-racial and socioeconomic differences. The documents identify that the further into the interior of the Pará Amazon, the fewer the offerings of inclusive components in the field of Special Education. It was noted in the PPCs studied that inclusive processes are extended to ethnic-racial issues, socioeconomic conditions, and the field of Special Education. However, in some circumstances, the inclusion of special education is little visible in the PPCs studied.
Keywords: Educação Especial Inclusiva; Formação docente; Projetos Pedagógicos de Curso; PPC’s; CNPQ::CIÊNCIAS HUMANAS